The Determinant of Employee's Performance: A Systematic Literature Review - Alean Kistiani Hegy Suryana; Jati Waskito; K Kussudyarsana (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
The purpose of this study is to analyze the determinants of employee performance. The methods used in this study are the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis) method and Bibliometric Analysis using Vosviewer. The data source was obtained from Scopus for the period 2015-2025. Based on the results of the literature that has been reviewed with the search results for "determinant of employee performance" , 941 journals were found. Then data filtering was carried out using the PRISMA method so that 49 papers were included in the category. Of the 49 articles that have been obtained using the PRISMA SLR Analysis, 10 journals will be selected that have the highest number of citations. The results of the study say that employee performance is influenced by a combination of individual and external factors. The main determinants that affect employee performance include self-efficacy, person-job fit, motivation, training and development, interactional fairness, employee well-being, effective leadership, and external crises. These factors work together to influence how well employees can perform their duties and contribute to the organization's goals.